Conventional vs. complex training: A set by set and sessional comparison of kinetic and kinematic variables - Talpey, S.; Young, W.; Saunders, N. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to evaluate moments and shear forces at the hip and knee during step ups and single leg squats. Subjects were 12 weight trained adults. Each subject performed 3 repetitions of step ups and single leg squats using 70% of 1 repetition maximum. 2 X 2 (lift X phase (eccentric/concentric)) repeated measures ANOVAs were performed for each dependent variable. Significant interaction effects (p<0.05) were observed for knee shear force, hip shear force, and hip moment. Main effects (p<0.05) for both lift and phase were observed for knee moment. The single leg squat produced greater hip and knee moments with less absolute weight. The single leg squat may be a better exercise for healthy individuals, but may be problematic for those with a hip or knee dysfunction.T he purpose of this study was to investigate the effects of complex sets on kinetic and kinematic variables in a countermovement jump (CMJ) compared to a conventional training session. Twenty-three recreationally trained males completed two familiarisation and two experimental conditions. No significant differences (p <0.05) occurred in the CMJ peak jump height, peak force, peak power and peak velocity obtained from three sets of four CMJ`s which either preceded (conventional training) or followed (complex training) three sets of four back squats with a five repetition maximal load.